Exploration of High Economic Value Microalgaes in The Mangrove Area of Pari Island, Seribu Islands, Jakarta - Hutari, Andri; An Nisaa, Ranti; Suhendra, Suhendra; Agustin, Yeni; Ayunda, Khairunisa Aprilia (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Mangrove areas are widely reported as a place of abundance of microalgae producing omega-3 docosahexaenoic acid (DHA) and other bioactive materials of high economic value from the genus Aurantiochytrium. The search for microalgae was carried out in the mangrove area of Pari Island, Seribu Islands, Jakarta, in April 2022 and identified at the Biology Education Laboratory, FKIP UHAMKA. The purpose of this study is part of the long-term goal of collecting new strains or isolates from the genus Aurantiochytrium and other members of the family Thraustochytriidae from forests in Indonesian mangroves. This research was conducted by isolating microalgae with the pure streaking method and identifying them morphologically. This study succeeded in obtaining eight isolates (UHA1, UHA3, UHA5, UHA6, UHA10, UHA11, UHA12, and UHA13) which in the appearance of colonies and microscopic morphology lead to the species Aurantiochytrium sp. One of the isolates obtained (UHA12) was cultivated by batch culture for five days in an Erlenmeyer flask using glucose, yeasts extract, and seawater as a medium. The result is that the dry biomass obtained is almost equivalent to that of the Aurantiochytrium sp. other famous